2021
DOI: 10.4028/www.scientific.net/ssp.314.155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrophobicity and Surface Potential of Silicon on SiO<sub>2</sub> Etching in Nanometer-Sized Narrow Spaces

Abstract: Wet etching in nanometer-sized three-dimensional spaces creates new challengesbecause of the scaling of semiconductor devices with complex 3D architecture. Wet etching withinspaces is affected by the mass transport of the etchant ions that are impacted by the hydrophobicityand surface potential of surface. However, the kinetics of chemical reactions within the spaces is stillunclear.In this paper, we studied the effect of hydrophobicity and surface potential of silicon surface on SiO2etching in nanometer-sized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
3
7
1
Order By: Relevance
“…Clearly, all results reveal linear relations between the etching length and the etching time, suggesting constant etching rates for wet Si etching in 2-D nanochannels. These findings align with previous observations in wet etching of TiN and SiO 2 -filled nanochannels 9,11 but are different from wet etching of Cr-filled nanochannels, 13 indicating that the wet KOH-Si etching reaction in the nanoconfinement is not limited by reactant/product diffusion but by the reaction kinetics.…”
Section: ■ Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Clearly, all results reveal linear relations between the etching length and the etching time, suggesting constant etching rates for wet Si etching in 2-D nanochannels. These findings align with previous observations in wet etching of TiN and SiO 2 -filled nanochannels 9,11 but are different from wet etching of Cr-filled nanochannels, 13 indicating that the wet KOH-Si etching reaction in the nanoconfinement is not limited by reactant/product diffusion but by the reaction kinetics.…”
Section: ■ Introductionsupporting
confidence: 91%
“…Therefore, their corresponding etching reaction kinetics and specificity may vary from those of bulk/plain surfaces or microscale confinements, and the transport of reactants and products of the etching reaction may also affect the reaction. As a result, nonuniform etching rate and different selectivities have been observed when features with different nanoconfinements are present on the same wafer, which cause serious challenges for etching control and thus significantly affect the fabrication yield and quality. , To properly address this challenge, efforts have been made on investigating wet etching reactions in nanoconfinements (WERIN) filled with a variety of materials and several factors that could affect the etching reaction have been proposed. Specifically, Okuyama et al studied diluted hydrofluoric acid (dHF) etching of SiO 2 -filled 2-D planar nanochannels and discovered that the etching length is a linear function of the etching time, suggesting a kinetics-limited reaction . They found that the resulting constant etching rate decreases with decreasing channel height and hypothesized that it is a result of reactant concentration changes due to electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the electrical double layer (EDL) formed within the capillary reduces the effective width for ionic diffusion. 16 Second, gas bubble entrapment and poor wetting of the solution prohibit solution infiltration. 17 Third, limited diffusion causes the insoluble intermediate precipitation and congestion at the trench, 18−20 yet none of the hypotheses have been proven with direct evidence.…”
mentioning
confidence: 99%
“…The potential causes of this unstripping phenomenon have been reported previously, and many hypotheses have been postulated. First, the electrical double layer (EDL) formed within the capillary reduces the effective width for ionic diffusion . Second, gas bubble entrapment and poor wetting of the solution prohibit solution infiltration .…”
mentioning
confidence: 99%